Digital Shadows: A Criminological Study of Cyber ​​Crime Law Enforcement in the Era of Technological Disruption - Sri Wulandari; Farisha Dian Prabaningtyas (Jurnal Ilmiah Dunia Hukum, 2026)
This study aims to examine cybercrime from a criminological perspective. The rapid development of information and communication technology has led to the growth of cybercrime, along with society's increasing dependence on digital technology. Cybercrime is a threat that cannot be ignored due to its widespread impact across various sectors of society, ranging from data theft and system sabotage, virus spread, electronic fraud, to politically motivated crimes and cyberterrorism. A criminological study of cybercrime is crucial in providing an understanding of the characteristics, motivations, and social impacts of these crimes. This study utilizes criminological theories to understand why individuals commit cybercrime and assesses the effectiveness of the role of law enforcement officials in Indonesia in combating it, based on the legal regulations of Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE), which was later amended by Law Number 19 of 2016 in conjunction with Law Number 1 of 2024 and Law Number 27 of 2022 concerning Personal Data Protection (PDP Law).